2007
DOI: 10.1007/s11858-007-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Early algebra and mathematical generalization

Abstract: We examine issues that arise in students' making of generalizations about geometrical figures as they are introduced to linear functions. We focus on the concepts of patterns, function, and generalization in mathematics education in examining how 15 third grade students (9 years old) come to produce and represent generalizations during the implementation of two lessons from a longitudinal study of early algebra. Many students scan output values of f(n) as n increases, conceptualizing the function as a recursiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0
59

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 19 publications
6
84
0
59
Order By: Relevance
“…These findings, suggesting language features as a means to provide Allen access to these algebraic tasks, echo findings from Carraher et al's [22] study. Essentially, Carraher et al [22] found that student developed conjectures as a mean to provide students explicit statements of mathematical relationships.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…These findings, suggesting language features as a means to provide Allen access to these algebraic tasks, echo findings from Carraher et al's [22] study. Essentially, Carraher et al [22] found that student developed conjectures as a mean to provide students explicit statements of mathematical relationships.…”
supporting
confidence: 81%
“…Recent findings suggest that young students are capable of constructing algebraic generalizations, paying attention to the explicit language and use of conjectures in solving operation problems [19][20][21][22]. Students as young as preschool-age have been found capable of transitioning their everyday experiences to mathematical experiences when developing an additive-subtractive inversion principle [19].…”
Section: Early Algebra and Mental Reversibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compõem esse panorama as realizações que comunicam o conceito de função como um texto que descreve uma regra (funcional) para determinar o valor de um elemento de uma posição arbitrária em uma sequência, com base no conhecimento dos seus elementos iniciais (CARRAHER; MARTINEZ; SCHLIEMANN, 2008). A construção e a validação dessa regra não são baseadas em uma inferência formal, ou seja, não são fundamentadas na realização de uma prova (demonstração), trata-se de processo indutivo "informal" que é legitimado como uma forma de argumentação no contexto da Escola Básica.…”
Section: Panorama Da Generalização De Padrõesunclassified
“…A different approach to early algebra, called the 'functional approach', uses numeric or geometric patterns to explore the relationships between quantities, variables and representations. One classic example is figuring out how many people could sit at restaurant tables made up of one, two, three or nine square tables pushed together [50]. Students readily understand the function and can iteratively calculate the number of people in each case.…”
Section: Current Directions In Educational Researchmentioning
confidence: 99%